Serum endocan levels, carotid intima-media thickness and microalbuminuria in patients with newly diagnosed hypertension - Sevil Fisekci Oktar; Ibrahim Guney; Sayeste Akkan Eren; Levent Oktar; Kenan Kosar; Zafer Buyukterzi; Ender Alkan; Zeynep Biyik; Said Sami Erdem (Clinical and Experimental Hypertension, 2019)
Background: Endocan is a particular protein of endothelial cells. The purpose of this study was to determine the relationship of serum endocan levels with carotid intima-media thickness (cIMT), inflammation, and microalbuminuria in patients with newly-diagnosed hypertension. Materials-Methods: This prospective study included 61 patients with newly-diagnosed hypertension (HT) and 30 controls. Endocan, microalbuminuria and cIMT measurements were taken from all patients. Results: The serum endocan levels, the mean cIMT and microalbuminuria levels of patients with HT were significantly higher than those of the control group (p < .0001, p = .015 and p < .001, respectively). Conclusion: We found that endocan levels were increased in our study. This increase in endocan levels shows a relation with cIMT and microalbuminuria, which are associated with endothelial dysfunction.